GAMBARAN INDEKS MASA TUBUH ANAK USIA 6 TAHUN YANG MENGKONSUMSI SUSU FORMULA DI SD MUHAMMADIYAH 01 KEC. MEDAN AREA, KOTA MEDAN, SUMATERA UTARA - Fitri, Edriani; Sutysna, Hendra; Airlangga, Eka; Damayanty, Amelia Eka (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Body Mass Index (BMI) is one of parameters to monitor childrenâs physical growth. It isÂ calculated of the body weight and height. Children aged 6 years is in active phase and more energy needed. Milk has rich of nutrients which affect the BMIÂ in children aged 6 years old. Objective: this studi aimed to obtain the description of BMI in children 6 years old who consume formula milk. Method: The study used descriptive cross-sectional design. Targeted populations were the students of Muhammadiyah Elementary School 01 in Medan Area Sub-district,Â Medan City, Sumatera Utara. Children who have congenital and chronic diseases, including infectious disease from the last 3 months were excluded. Results: There were 90 children participated in the study. The students who consumed formula milk most frequently was underweight (41; 45,6%), normoweight (33; 36,7%), and overweight (16; 17,8%). Conclusion: Body Mass Index in 90 children aged 6 years who consume formula milk was described.Keywords: Body Mass Index, Formula Milk, 6-Year-Old Child.Â